2021
DOI: 10.1186/s12905-021-01536-6
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of reproductive risk factors disclosed the heterogeneity of receptor-defined breast cancer subtypes among Tanzanian women

Abstract: Background Recent epidemiological studies suggest that reproductive factors are associated with breast cancer (BC) molecular subtypes. However, these associations have not been thoroughly studied in the African populations. The present study aimed to investigate the prevalence of BC molecular subtypes and assess their association with reproductive factors in Tanzanian BC patients. Methods This hospital-based case-only cross-sectional study consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Tumor biomarkers including ER, PR, and HER2/neu were determined by immunohistochemistry upon the formalin fixed paraffin‐embedded blocks of BC tissues as described elsewhere. 13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor biomarkers including ER, PR, and HER2/neu were determined by immunohistochemistry upon the formalin fixed paraffin‐embedded blocks of BC tissues as described elsewhere. 13 …”
Section: Methodsmentioning
confidence: 99%
“…The BC samples were histologically and pathologically examined at Muhimbili National Hospital (MNH), Bugando Medical Center (BMC), or Kilimajaro Christian Medical Center (KCMC). Tumor biomarkers including ER, PR, and HER2/neu were determined by immunohistochemistry upon the formalin fixed paraffin‐embedded blocks of BC tissues as described elsewhere 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details about the ORCI facility are described elsewhere. 26 , 27 To be eligible for this study, patients had to fulfill the following inclusion criteria: being indigenous Tanzanian, and having a complete histopathological report that shows the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor‐2 (HER‐2) statuses. The exclusion criteria were: being non‐indigenous Tanzanian, failure/denial to sign a consent form, and having incomplete histopathological report in the hospital medical file.…”
Section: Methodsmentioning
confidence: 99%
“…3 Similarly study from Tanzania found that women who had their first full-term pregnancy at <30 years were more likely to have luminal-B and triple negative subtypes relative to luminal-A subtype. 4 Another study done in Cairo also revealed that the most common risk factors for breast cancer were family history of breast cancer and using hormonal contraceptives. 5 Breast cancer poses a substantial public health threat in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%